Shaykh Yusuf of Macassar; Scholar, Sufi, National Hero: Towards Constructing Local Identity and History at the Cape - Armien Cassiem (Kawalu: Journal of Local Culture, 2017)
This paper focuses on the Origins and Malaya presence of Islam in both ritual practices and daily life of modern day Islam as practiced by Muslims in Cape Town, South Africa. It also tries to capture the presence of Shaykh Yusuf s short time spent at the Cape, 1694 - 1699, and how this period of his life gives expression to local history, storytelling, tradition and meaning to Islam in contemporary Cape Town. Keywords: Shaykh Yusuf, Macassar, South Africa, Ritual Practices, Local Identity